Small, uniform, and rarely collected—an integrated taxonomic revision of Afromicracis bark beetles (Coleoptera, Scolytinae) - Jordal, Bjarte (Zootaxa, 2021)
Afromicracis is typically found in small twigs and lianas, on the African mainland from Ghana to Ethiopia and south to the Cape region. Due to their small and uniform shape, previous classifications were largely misleading. The genus is revised with a total of 16 valid species in the genus. Seven species are described as new to science: Afromicracis brevipilosa sp. nov. and Afromicracis crinita sp. nov., both from South Africa, Afromicracis concava sp. nov. from Cameroon, Afromicracis crassa sp. nov. and Afromicracis densisetosa sp. nov. from Tanzania, Afromicracis depilata sp. nov. from Uganda, and Afromicracis ghanaensis sp. nov. from Ghana. Molecular data document deep divergence and limited morphological evolution for this genus. A key and photographs are provided to enable identification of Afromicracis species.